PENGARUH RASIO KESEHATAN BANK TERHADAP KINERJA KEUANGAN BANK PERKREDITAN RAKYAT DI KABUPATEN DELI SERDANG TAHUN 2018 - 2022 - Lukman Hakim Siregar; Kristin Tamba (Bisnis-Net, 2023)
This research aims to find out how the bank health ratio influences the financial performance of Rural Banks in Deli Serdang Regency. This data collection technique is to process quantitative data, which uses secondary data, namely quarterly financial reports for the 2018-2022 period from published reports from the Financial Services Authority. The objects of this research are 15 Rural Banks in Deli Serdang Regency. The data analysis method is using the RGEC method, namely: Risk Profile, Good Corporate Governance, Earnings, and Capital. Data analysis uses descriptive statistical analysis, namely data normality test, hypothesis test, autocorrelation test, f test, t test and multiple linear coefficient of determination test. The results of this research explain that the research data is not normally distributed. The results of the Autocorrelation Test have a relationship between variable Y and variable Hypothesis testing explains that the CAR and ROA variables have a positive effect and the BOPO variable has a negative effect on ROA. The coefficient of determination is 1.069 < 3.12 or Sig value. 0.368 > 0.05. So it can be concluded that there is no influence of X1, X2 and X3 simultaneously on Y (Net Profit). Keywords : Bank Health Ratio, Financial Performance, Rural Bank.